Methods in Quaternary Ecology #6. Cladocera - Hann, B. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary Cladocera are among the best represented groups of aquatic invertebrates that leave fossils in lake sediments. The skeletal fragments of Cladocera are abundant, can beidentified to species in most cases, and represent taxa from a variety of ecologicalniches in a lake. Unlike more conventional paleoecological indicators such as pollen orbeetles, Cladocera are not useful directly inpaleoclimatic reconstructions. Instead,Cladocera microfossii assemblages am uesiused to reconstruct past lacustrine environments, to investigate the effects of human disturbance (eutrophication, acidification, contaminants), and to assess long-term population and community changes. Improved understanding of the ecological tolerancesof living Cladocera, increased comparisons with analogue communities, and application of multivariate analytical methods will expand our interpretive capabilities for both modern and fossil assemblages. Once we understand how and why cladoceran communities responded to environment alevents in the past, we may be better able to predict the direction and magnitude of future change.